The Tradition of Ngaibakan Benda Pusaka in the Pulo Traditional Village: Symbolic Negotiation of Islam and Local Wisdom in the Construction of Collective Identity - Luk Luk Atin Marfuah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
This study examines the Ngaibakan benda pusaka ritual (heirloom bathing ceremony) in Kampung Adat Pulo, Garut Regency, West Java, as a site of symbolic negotiation between Islamic orthodoxy and local wisdom in constructing collective identity. Despite intensifying Islamic purification movements and modernization pressures, this indigenous community maintains syncretic religious practices that harmoniously integrate Islamic values with pre-Islamic cosmology. Using an ethnography of communication approach, data were collected through six-month participant observation (May–October 2024), in-depth interviews with 14 key informants, and documentation analysis. Findings reveal three mechanisms of collective identity reproduction: ritualized collective memory through narrative reactivation of ancestral genealogy, symbolic boundary maintenance via sacred objects and spatial configuration, and embodied value transmission through performative participation. The ritual demonstrates 'dialogical syncretism a dynamic negotiation process whereby Islamic theology and indigenous cosmology mutually transform each other without either dominating the other, achieved through cosmological stratification, symbolic reinterpretation, and theological legitimation. This study contributes to communication scholarship by demonstrating how ritual communication constitutes social reality, and to Islamic studies by offering a contextualized da'wah model that honors cultural diversity within theological unity.